An Italian Retrospective Survey on Bone Metastasis in Melanoma: Impact of Immunotherapy and Radiotherapy on Survival - Mannavola, Francesco; Mandala, Mario; Todisco, Annalisa; Sileni, Vanna Chiarion; Palla, Marco; Minisini, Alessandro Marco; Pala, Laura; Morgese, Francesca; Di Guardo, Lorenza; Stucci, Luigia Stefania; Guida, Michele; Indini, Alice; et al. (Frontiers in Oncology, 2020)
Background: We performed a multicenter retrospective observational study to investigate the impact of clinical-pathological features and therapeutic strategies on both complications and survival of patients with bone metastases from malignant melanoma. Patients and Methods: A total of 305 patients with melanoma and radiological evidence of bone metastases were retrospectively enrolled from 19 Italian centers. All patients received conventional treatments in accordance with each own treating physician’s practice. Both univariate and multivariate models were used to explore the impact of melanoma features including skeletal-related events (SREs), and different treatments on both overall survival (OS) and time-to-SREs. The chi-squared test evaluated the suitability of several parameters to predict the occurrence of SREs. Results: Eighty-three percent of patients had metachronous bone metastases. The prevalent (90%) bone metastatic site was the spine, while 45% had involvement of the appendicular skeleton. Forthy-seven percent experienced at least one SRE, including palliative radiotherapy (RT) in 37% of cases. No melanoma-associated factor was predictive for the development of SREs, although patients receiving early treatment with bone-targeted agents showed 62% lower risk and delayed time of SRE occurrence. Median OS from the diagnosis of bone metastasis was 10.7 months. The multivariate analysis revealed as independent prognostic factors number of bone metastases, number of metastatic organs, baseline LDH levels and treatment with targeted therapy or immunotherapy. Sub-group analyses showed the best OS (median 16.5 months) in the subset of patients receiving both immunotherapy and palliative RT. Conclusion: Based on our results, patients undergoing immunotherapy and palliative RT showed an OS benefit suggestive of a possible additive effect. The apparent protective role of bone targeting agent use on SREs observed in our analysis should deserve prospective evaluation.